O Paladino da Boa Causa”: Manuel Querino e a questão racial na Bahia (1905-1923) - Souza, Michelle Dantas Reis (2015)
Baiano, who was born in Santo Amaro da Purification, graduated in design from the Academy of Fine Arts, where he taught, and a founding member of the Bahia Geographic and Historic Institute, Manuel Querino (1851-1923) devoted much of his career to research and highlight the contribution African in national and Bahia training. From 1905, began publishing his work on the topic in the Bahia Institute magazine until 1923, the year he died. This period did not provide a favorable setting for the one who chose to study about the black in Brazil, since the discourses on racial inferiority, still had acceptance by national intellectuals. Thus, this thesis aims to understand the positioning of this author in combating scientific racism of the time and his activism in development of a national identity and, above all, Bahia, which included African descent as a fundamental element. In addition, we seek to demonstrate the main counterpoints between words that Bahian author about the racial question and the doctor Maranhão Nina Rodrigues (1862-1906), who was considered one of the leading scholars of scientific racism in the country. Both have focused on common themes, such as the issue of slave resistance, religion and culture of African origin; developing different interpretations. Thus, we seek to also examine the extent to which Manuel Querino sought to answer his contemporary medical school.